Lifestyle among former cancer patients in Brazil in 2013 - Gulnar Azevedo e Silva (Ciência & Saúde Coletiva, 2016)
People who have been diagnosed with cancer tend to adopt healthier lifestyles. This study analyzes the prevalence of smoking, eating fruits and vegetables, exercise and the use of alcoholic beverages among individuals who reported to have been diagnosed with cancer in the PNS (Pesquisa Nacional de Saúde or National Health Survey). The prevalence and corresponding 95% confidence intervals were calculated for consuming fruits and vegetables, sedentary lifestyle (no exercise), use of alcoholic beverages, being overweight and tobacco use. The associa-tion between having received a diagnosis of cancer and the risk and protection factors was analyzed using a Poisson regression, adjusted by sociodemographic variables and other chronic comorbidities. The analyses were stratified by time since the diagnosis and the type of cancer related to the factors analyzed. The types of cancer most often reported were breast and cervix in women, and prostate and stomach in men. Among those who had cancer diagnoses, there was a higher consumption of fruits and vegetables, higher proportion of ex-smokers, however, increased use of alcohol. There was no difference in the frequency of exercise or incidence of being overweight between the two groups. Measures to promote health and prevent chronic diseases should be implemented in the follow-up of people who have had cancer, in an effort to ensure integrated healthcare.